Minimum wages and the fate of Indonesian young workers - Izzun Nafiah (Department of Development Economics, Universitas Sriwijaya, 2020)
Government policies that are directly related to the relationship between workers and companies are determining minimum wages. The effect of this minimum wage becomes more varied for developing countries with large populations such as Indonesia. Young workers have sensitive effect to fluctuation of the minimum wage policy, whereas the percentage of Indonesia young workers is more than 20 percent of the total workforce in 2015-2019. Therefore, the aim of this research is to analyze the effect of minimum wage policies on the status of young workers in Indonesia using quantitative data from the National Labour Force Survey (Sakernas) 2015-2019 with the multinomial logit analysis method. The results of this study are an increase in the minimum wage decreases the probability of young workers to have status as paid workers in the covered sector. In urban areas, an increase in the minimum wage increases the probability of young male workers being unemployed and decreases the probability being self-employed. On the other hand, an increase in the minimum wage causes female urban workers reducing the probability of being unemployed and increasing the probability of them being self-employed. Therefore, the minimum wage policy must be balanced with strengthen the education and training and also consider policies that increase youth labor market opportunities but do not increase employer costs for young workers. On the other hand, the government must be continuous to improve policies that support the progress of informal sector, for example in terms of providing capital, reducing loan interest rates, etc.